2005
DOI: 10.1073/pnas.0503855102
|View full text |Cite
|
Sign up to set email alerts
|

Blood–testis barrier dynamics are regulated by an engagement/disengagement mechanism between tight and adherens junctions via peripheral adaptors

Abstract: In the mammalian testis, the blood-testis barrier (BTB), unlike the blood-brain and blood-retina barriers, is composed of coexisting tight junctions (TJs) and adherens junctions (AJs). Yet these junctions must open (or disassemble) to accommodate the migration of preleptotene and leptotene spermatocytes across the BTB during spermatogenesis while maintaining its integrity. In this report, we show that the BTB utilizes a unique ''engagement'' and ''disengagement'' mechanism to permit the disruption of AJ that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 43 publications
7
90
0
1
Order By: Relevance
“…23 In addition, the structural association of γ-catenin, an AJ adaptor, and ZO-1, a TJ adaptor, is weakened after treatment of rats using adjudin, which is shown to have a role in disturbing the AJ without compromising the TJ in the testes. 3,24 These findings substantiate the significance of adaptors that mediate cross-talk between different junction types in the testes. Apart from that, other functions are recently uncovered for adaptors, including their participation in cytokine signaling in the testes and immune-related activities 25,26 Based on this emerging evidence, adaptors are proteins with diversified physiological functions in maintaining spermatogenesis, in particular the events of junction restructuring.…”
Section: Nos/no In Junction Dynamicssupporting
confidence: 69%
“…23 In addition, the structural association of γ-catenin, an AJ adaptor, and ZO-1, a TJ adaptor, is weakened after treatment of rats using adjudin, which is shown to have a role in disturbing the AJ without compromising the TJ in the testes. 3,24 These findings substantiate the significance of adaptors that mediate cross-talk between different junction types in the testes. Apart from that, other functions are recently uncovered for adaptors, including their participation in cytokine signaling in the testes and immune-related activities 25,26 Based on this emerging evidence, adaptors are proteins with diversified physiological functions in maintaining spermatogenesis, in particular the events of junction restructuring.…”
Section: Nos/no In Junction Dynamicssupporting
confidence: 69%
“…Seminiferous tubules used for studies reported herein were isolated from adult rat testes and were shown to be contaminated with negligible Leydig cells as reported previously (31). Seminiferous tubule and germ cell lysates were prepared in an IP buffer (50 mM Tris-HCl, 150 mM NaCl, 1% Nonidet P-40 (v/v), 1 mM EGTA, 1 mM phenylmethylsulfonyl fluoride, 1 mM sodium orthovandate, 1 g/ml leupeptin and 1 g/ml aprotinin, pH 7.4) as described (32).…”
Section: Conjugation Of Anti-laminin ␣3 and ␥3 Igg With Alexa Fluor 4mentioning
confidence: 99%
“…Co-immunoprecipitation (Co-IP) and Immunoblotting-To study the binding partners of laminin ␥3 as well as other interacting proteins in rat testes, co-IP was performed using lysates of either seminiferous tubules or germ cells as described previously (31). Seminiferous tubules used for studies reported herein were isolated from adult rat testes and were shown to be contaminated with negligible Leydig cells as reported previously (31).…”
Section: Conjugation Of Anti-laminin ␣3 and ␥3 Igg With Alexa Fluor 4mentioning
confidence: 99%
“…Even though occludin and cadherin at the BTB have no direct protein-protein interaction as demonstrated by coimmunoprecipitation, they are linked via their peripheral adaptors, such as ZO-1 and catenins. 89 This finding is not entirely unexpected since at the early stage of TJ assembly, ZO-1 was shown to associate with catenins in MDCK cells. 90 Besides, ZO-1 also serves as a cross-linker between the cadherin/catenin protein complex and the actin-based cytoskeleton in nonepithelial cells.…”
Section: Btb Dynamicsmentioning
confidence: 73%
“…In essence, ZO-1 was no longer associated with catenins, and as such, occludin and N-cadherin as well as their adaptors, ZO-1 and γ-catenin were diffusing away from the BTB site. 89 Yet, their association was reestablished by day 7 after treatment when germ cells (e.g., elongating/elongate spermatids and some round spermatids) were depleted from the epithelium. Based on such timely dissociation between TJ and AJ protein complexes in the seminiferous epithelium, an "engagement and disengagement" theory was proposed to describe the unique mechanism employed by the testis to facilitate germ cell movement pertinent to spermatogenesis 89 (Fig.…”
Section: Btb Dynamicsmentioning
confidence: 99%